Validation of a Liquid Chromatographic Method for Determination of Sulphadoxine and Pyrimethamine in Whole Blood Spotted on Filter Paper (2012)
ABSTRACT: Objective: to validate an analytical method for simultaneous determination and quantification of sulphadoxine and pyrimethamine in human blood dried onto filter paper, whose cost and analysis time can be reduced. Methods: whole blood spotted on filter paper of a healthy volunteer and solutions of sulphadoxine-pyrimethamine standard mixture were used. HPLC separations were carried out on Agilent equipment using a LiChrospher® column C18 with a mobile phase acetonitrile/0.1 M potassium phosphate buffer at pH 3.0 (1:1) for eight minutes under isocratic conditions. A flow rate of 0.7 mL/min, and a 20 mL volume injection were used. External standard method for quantitation of analytes was used. Results: the HPLC method described for the simultaneous determination of sulphadoxine and pyrimethamine in 100 mL of whole blood spotted on filter paper has been found to be linear, precise, accurate and selective. In this method, the sample preparation is simple using liquid liquid extraction, and HPLC with ultraviolet detection is used. Conclusions: a simple, fast and sensitive method for determination of sulphadoxine and pyrimethamine in human blood dried onto filter paper was validated. This method can be used for the monitoring of both metabolites in pharmacokinetic and clinical studies.